Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 476: 15



Work Step by Step

RECALL: $(g-f)(x) = g(x) - f(x)$ Using the formula above gives: $(g-f)(x) = (x^2-5) -(-2x+3) \\(g-f)(x)= x^2-5-(-2x)-3 \\(g-f)(x)= x^2-5+2x-3 \\(g-f)(x)= x^2+2x-8$ Thus, to evaluate the given expression, substitute 1 to the equation above to obtain: $g(1) -f(1) \\= (g-f)(1) \\= 1^2+2(1)-8 \\=1+2-8 \\=3-8 \\=-5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.